Patients' Expectations of Benefits From Large-Panel Genomic Tumor Testing in Rural Community Oncology Practices. (2021) - Anderson, Eric C.; DiPalazzo, John; Edelman, Emily; Helbig, Petra; Reed, Kate; Miesfeldt, Susan; Thomas, Christian; Lucas, F. Lee; Fenton, Anny T. H. R.; Antov, Andrey; Hall, Michael J.; Roberts, J. Scott; et al.
Abstract : PURPOSE: Large-panel genomic tumor testing (GTT) is an emerging technology that promises to make cancer treatment more precise. Because GTT is novel and complex, patients may have unrealistic expectations and limited knowledge of its benefits. These problems may limit the clinical value of GTT, but their prevalence and associated factors have not been explored. METHODS: Patients with cancer enrolled in a large initiative to disseminate GTT in community oncology practices completed surveys assessing their expectations, knowledge, and attitudes about GTT. The study sample (N = 1, 139) consisted of patients with a range of cancer types (22% gynecologic, 14% lung, 10% colon, 10% breast, and 46% other malignancies) and cancer stages (4% stage I, 3% stage II, 15% stage III, and 74% stage IV). Mean age was 64 years (standard deviation = 11); 668 (59%) were women; 71% had no college degree; 57% came from households with less than $50, 000 US dollars household income; and 73% lived in a rural area. RESULTS: Generally, patients had high expectations that they would benefit from GTT (M = 2.81 on 0-4 scale) and positive attitudes toward it (M = 2.98 on 0-4 scale). Patients also had relatively poor knowledge about GTT (48% correct answers on an objective test of GTT knowledge). Greater expectations for GTT were associated with lower knowledge (b = –0.46; P < .001), more positive attitudes (b = 0.40; P < .001), and lower education (b = –0.53; P < .001). CONCLUSION: This research suggests patients have high expectations that they will benefit from GTT, which is associated with low knowledge, positive attitudes, and low education. More research is needed to understand the concordance between expectations and actual clinical outcomes.